Yentl [videorecording (DVD)] - Streisand, Barbra; Patinkin, Mandy; Irving, Amy, 1953-; Persoff, Nehemiah, 1919-; Singer, Isaac Bashevis, 1904-1991 (20th Century Fox Home Entertainment, 2009)
Yentl Mendel is the boyish daughter and only child of long widowed Rebbe Mendel. He teaches Talmud to local boys and secretly to Yentl since girls are not allowed to learn the law. When her father dies, Yentl is left all alone. She makes the momentous decision to leave the village and, disguised as a boy and calling herself Anshel, she seeks and gets admitted to a Yeshiva to study. She befriends Avigdor who is engaged to Haddas. Her family calls off the wedding when they discover Avigdor's brother committed suicide. Anshel then finds 'him'-self in the awkward position of being called into service as substitute bridegroom. But Haddas still wants Avigdor. After numerous complications, including Avidor and Yentl falling in love with each other and she telling him her secret, everyone gets what they want in life. Anshel, now Yentl once again, goes off to America to pursue her dream of serious study in Yeshiva, where she will be able to study without needing to hide her identity as a woman.